Study of Ki-67 Expression in oral lichen planus precancerous lesions (An immunohistochemical study) (Journal of Hama University, 2019)
lichen planus is a chronic, relatively common, dermal mucosa disease. The World Health Organization (WHO) has introduced lichen planus as a premalignant condition. The Ki-67 antigen is expressed in all the phases of the cellular cycle in proliferative cells. Different studies have suggested the relationship between incidences of malignancy in precancerous lesions and the occurrence of this protein.This study aimed to evaluate the Ki-67 expression in oral lichen planus using an antibody the Ki-67 protein, and compare it with Ki-67 expression in normal oral epithelium as control.The sample consisted of 20 formalin_fixed, paraffin_ embedded specimens of oral lichen planus lesions and 20 normal oral epithelium  that were conventionally stained with H&E and immunohistochemically stained with a polyclonal Ki-67 antigen antibody.The Ki-67 expression was found in all the cases of normal oral epithelium studied and was found to be restricted to the basal layer of the epithelium. In Lichen planus cases, the Ki-67 expression was more than the normal mucosa.Considering Ki-67 is a proliferation marker, the increased expression of Ki-67 in the oral lichen planus group’s epithelium indicates a high proliferation rate in lichen planus lesions.